ANALISIS PROFITABILITAS USAHATANI TEMBAKAU DI KELOMPOK TANI TARUNA TANI DESA LEGOKSARI KECAMATAN TLOGOMULYO KABUPATEN TEMANGGUNG - Murti, Sintiyah Ari; Santoso, Siswanto Imam; Budiraharjo, Kustopo (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 13 No 3 (2019): Vol. 13, No. 3, 2019DO - 10.24843/SOCA.2019.v13.i03.p07, 2019)
Tobacco is the raw material for making cigarettes and has a large contribution in agricultural development, so many farmers who run tobacco farming but have not considered the profit or profitability at the farmer level.The purpose of the study to analyze the profitability of tobacco farming and the influence factor of land area, production and selling prices to ward the profitability of tobacco farming in Taruna Tani group. The reasearch was held form October until December of 2018 at Taruna Tani group Legoksari village, Tlogomulyo subdistrict of Temanggung regency. A survey method was applied as the research method and the sample was taken by census. Questionnaires and interviews were used to collect the data. The data analysis were using descriptiv, quantitativ, one sample t-test and multiple linear regression. This study shows the results that the average production costs in Taruna Tani group was Rp. 25,550,771.90/MT, the average revenue was Rp. 47,564,525.46/MT, the average income was Rp. 22,055,376.06/MT and the average profitability was 85,25%. It can be said that tobacco farming in the Taruna Tani group is profitable. The Land area, the production and the selling price have a simultane effect on profitability while partial production and selling prices have a significantly influence and land area doesn’t significantly influence the profitability of tobacco farming